Robust Channel Estimation for MIMO-OFDM-IM Full-Duplex Relaying under Residual Self-Interference in Time-Varying Fading - Mata, Tanairat; Boonsrimuang, Pisit (My University, 2026)
Full-duplex relaying can significantly improve spectral efficiency in vehicular communications, but its practical performance is constrained by residual self-interference (SI) and rapidly time-varying channels. This work proposes a Walsh–Hadamard and null (WHN) pilot with maximum likelihood (ML)–based channel estimation (CE) for MIMO OFDM-IM full-duplex relays. Unlike prior designs that prioritize either low complexity or estimation accuracy, the proposed WHN scheme improves the performance–complexity trade-off by leveraging asymmetric pilot intervals and structured orthogo nalization. Two widely recognized baselines are considered for comparison: (i) cyclic-shifted Zadoff–Chu (CS-ZC) preamble pilots representing the low-complexity DFT-domain benchmark, and (ii) scattered pilot-and-null (PN) patterns with ML refinement representing the high-accuracy benchmark used in LTE/5G systems. Results reveal a consistent carrier-to-noise power ratio (CNR)-dependent crossover: WHN outperforms CS-ZC when CNR≥28dBandsurpassesPNundermoderate-to-high mobility. At 35 dB CNR, WHN provides up to 35% BER reduction with only 29% complexity overhead. A standard-compliant link budget analysis further indicates non-trivial coverage gains under the evaluated Doppler regimes and considered residual SI model. All simulation assumptions, Doppler profiles, and SI models follow V2X guidelines, and results are validated across multiple random seeds. Overall, WHN offers a complexity-aware CE solution for full-duplex V2X systems.
Keywords: Channel estimation; Full-duplex relaying; OFDM-IM; Self-interference cancellation; Vehicular communications